Assessment of Radioactivity and Radiological Hazard of Different Food Items Collected from Local Market in Bangladesh (Journal of Bangladesh Academy of Sciences, 2020)
Sixteen samples in three categories vegetables, cereals (rice, wheat, maize, pulse) and powdered milk were collected from local markets (Dhaka city) in Bangladesh and analyzed by using High Purity Germanium (HPGe) Detector for the assessment of natural and artificial radioactivity. In vegetables (potato, raw banana, giant taro, red amaranth), the average activity concentrations of 232Th, 226Ra, and 40K were found to be 37.82±11.57, 54.93±9.98 and 617.43±65.69 Bqkg-1 respectively, for cereals (rice, wheat, maize, pulse) 24.01±3.67, 31.46±4.00 and 474.83±27.68 Bqkg-1 respectively and for milk samples 15.01±3.65, 26.73±6.77 and 494.21±38.71 Bqkg-1 respectively. The average values of outdoor annual effective dose were found to be 92.18, 61.19 and 52.37μSvy-1 in vegetables, cereals and milk samples respectively. No artificial radionuclide was found in any of these samples. The average value of radium equivalent activity in all samples was 113.89 Bqkg-1 which was less than maximum permissible value 370 Bqkg-1. The values of external hazard indices for vegetables, cereals and milk samples varied from 0.31 to 0.66, 0.17 to 0.40 and 0.11 to 0.36 respectively which is less than unity in all samples that indicate the non-hazardous nature of the samples. The average values of annual effective ingestion dose rate from foods (for adult) were 274.33 μSvy-1, 533.60μSvy-1, and 132.73μSvy-1for 232Th, 226Ra and 40K respectively. These data would be useful to establish a baseline for natural radioactivity concentrations in food items consumed in Bangladesh.Journal of Bangladesh Academy of Sciences, Vol. 43, No. 2, 141-148, 2019